Prevalence of depression and its correlation with anxiety, headache and sleep disorders among medical staff in the Hainan Province of China - Lu, Guangshuang; Xiao, Shaobo; He, Jiaji; Xie, Wei; Ge, Wei; Meng, Fanchao; Yang, Ying; Yu, Shengyuan; Liu, Ruozhuo (Frontiers in Public Health, 2023)
Objective: This cross-sectional survey aimed to investigate the prevalence of depression among medical staff and its risk factors as well as the association between depression, anxiety, headache, and sleep disorders. Methods: Stratified random cluster sampling was used to select medical staff from various departments of four hospitals in Sanya City. The Self-Rating Depression Scale (SDS), Self-Rating Anxiety Scale (SAS), and Pittsburgh Sleep Quality Index (PSQI) were used to quantitatively assess depression, anxiety, and sleep disorders. Correlation and regression analyses were performed to determine factors affecting the depression occurrence and scores. Results: Among 645 medical staff members, 548 (85%) responded. The 1-year prevalence of depression was 42.7% and the prevalence of depression combined with anxiety, headache, and sleep disorders was 23%, 27%, and 34.5%, respectively. The prevalence of depression in women, nurses, the unmarried or single group, and the rotating-shift population was significantly higher than that in men (48.3% vs. 27.1%, odds ratio OR=2.512), doctors (55.2% vs. 26.7%, OR=3.388), the married group (50.5% vs. 35.8%, OR=1.900), and the day-shift population (35.2% vs. 7.5%, OR=1.719). The occurrence of depression was correlated with anxiety, sleep disorders, headache, and migraines, with anxiety having the highest correlation (Spearman’s Rho = 0.531). The SDS was significantly correlated with the SAS and PSQI (Spearman’s Rho = 0.801, 0.503) and was also related to the presence of headache and migraine (Spearman Rho = 0.228, 0.159). Multiple logistic regression indicated that nurse occupation and anxiety were risk factors for depression, while grades of anxiety, sleep disorders and nurse occupation were risk factors for the degree of depression in multiple linear regression. Conclusion: The prevalence of depression among medical staff was higher than that in the general population, especially among women, nurses, unmarried people, and rotating-shift workers. Depression is associated with anxiety, sleep disorders, headache, and migraines. Anxiety and nursing occupation are risk factors for depression. This study provides a reference for the promotion of occupational health among medical professionals.